2009
DOI: 10.1080/19368620903235795
|View full text |Cite
|
Sign up to set email alerts
|

Travelers' Intent to Use Mobile Technologies as a Function of Effort and Performance Expectancy

Abstract: Due to the nature of the tourism product (inherently experiential, intangible, and heterogeneous) and the substantial geographical distances, trial prior to the purchase decision is almost impossible. These kinds of distances could be overcome by information about the product, which is available in advance and can be gathered by the consumer. The upsurge of mobile technology is providing great flexibility for the tourism industry and travelers who have hierarchical needs for information beyond the extent or ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 43 publications
3
43
1
4
Order By: Relevance
“…Behavioral intention is regarded as one of the most powerful predictors of behavior, with Oh, Lehto, and Park (2009) noting that a positive relationship between behavioral intention and use behavior lends support to the assumption that intention to use can be used as an important proxy of travelers' future device use. The assumption is that a person's 170 acceptance of a technology is generally determined by his or her own positive or negative intention towards using that technology (Yousafzai et al, 2007).…”
Section: Attitudes and Intention To Usementioning
confidence: 99%
“…Behavioral intention is regarded as one of the most powerful predictors of behavior, with Oh, Lehto, and Park (2009) noting that a positive relationship between behavioral intention and use behavior lends support to the assumption that intention to use can be used as an important proxy of travelers' future device use. The assumption is that a person's 170 acceptance of a technology is generally determined by his or her own positive or negative intention towards using that technology (Yousafzai et al, 2007).…”
Section: Attitudes and Intention To Usementioning
confidence: 99%
“…Indeed, the nature of tourism as an inherently nomadic activity aligns well with the utility provided by mobile devices that are relatively small, portable, and offer a high degree of flexibility for the traveler (Oh, Lehto, & Park, 2009). It has been observed that the tourist experience can be enhanced through the delivery of various information services using mobile devices such as the smartphone-an activity that has the potential to change traveler behavior (Wang, Park, & Fesenmaier, 2011).…”
Section: Mobile Devices In Tourismmentioning
confidence: 99%
“…They noted that the traveler would potentially be able to access generally available Internet-based information that had been personalized (such as tourist attractions, guides, and means of transport), or specific information that might be sourced uniquely from travel partners and marketers. Oh et al (2009) explored traveler intentions for using mobile devices while on a trip and identified the main benefits that might be realized are the device being used as an organizer, how it facilitated Internet access, and its use as a communication tool. Such benefits were noted to be for personalized use that allowed information exchanges to be enacted in real time, from any location, and with particular relevance to the traveler.…”
Section: Mobile Devices In Tourismmentioning
confidence: 99%
“…Mobile apps provide various potentials for applications for tourists and travellers, including booking features, information provision and intense interaction channels with diverse tourism services (Oh, Lehto, & Park, 2009). On the one hand, on the basis of mobile technologies tourism organisations are able to provide better services to their customers like location based services and interactive search tools (Anacleto, Figueiredo, Almeida, & Novais, 2014;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%